Pharmacovigilance in Homoeopathy—Need of the Hour: A Narrative Review - Singh, Priya (Homœopathic Links, 2022)
Background Homoeopathy is the newest art and science of healing. Like conventional medicine, pharmacovigilance is an important aspect of homoeopathy. There is a paucity of knowledge and ignorance among the practitioners. The necessity is to create awareness and encourage the homoeopathic professionals regarding drug safety surveillance, documentation and reporting of adverse events.Methods A web-based online search from databases, journals, bibliographic resources regarding the practice of pharmacovigilance in homoeopathy was done. Articles and publications till January 2021 along with literature from homoeopathic books were analysed.Results Data on adverse drug reactions (ADRs) and events in homoeopathy have been collected and reported in European countries. In India, of late these terminologies are being acknowledged among a group of homoeopathic practitioners only. Still, a dearth of cognizance on the subject exists and little reporting is done. People usually do not relate such adverse reactions to the use of homoeopathic medicines. For scrutinising the same, the Ministry of AYUSH, Govt. of India, has taken an initiative for Pharmacovigilance of Ayurveda, Siddha, Unani & Homoeopathy systems of medicine for reporting and taking measures against ADR and objectionable advertisements. The probable risk factors and ways to prevent ADR and benefits of pharmacovigilance in homoeopathic practice could be deduced.Conclusion Homoeopathy is a widely followed system of medicine that is quite popular among the common people. The need of knowledge and promotion of suspected ADR reporting should be emphasised to increase the credibility of homoeopathy among the scientific community. Also, the profession should refrain from misleading and objectionable advertisements in print and electronic media.
Keywords: pharmacovigilance; homoeopathy; adverse drug reactions; AYUSH